(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Engineering Sciences Series, 2026)
In most countries worldwide, ensuring the power quality (PQ) has become a critical issue for power systems, including industrial and urban distribution networks. To overcome these problems, the active power filter (APF) is widely used in distribution networks and industrial networks. The active filter’s controller consists of two main components: one dedicated to generating the reference current, and the other responsible for producing the control signal for the inverter. This unit analyzes the harmonic components, subsequently generating compensating reference currents through various control systems, such as a proportional-integral (PI) controller. Using of evolutionary algorithms especially, particle swarm optimization (PSO) and salp swarm algorithm (SSA), to determine the optimal parameters of APF and the gains of PI controller (Kp,Ki) has been presented in this paper. The simulation results show the effectiveness of the proposed algorithms and achieve a good performance under a variable load. In a related context, the total harmonic distortion THD for current supply has been minimized from 11.5% to 1.99%, and the voltage of DC-link has a stable value with zero deviation from reference value using SSA.